2021
DOI: 10.1002/cam4.3971
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of structured palliative care versus standard supportive care for patients enrolled in phase 1 clinical trials

Abstract: Purpose Patients enrolled in Phase 1 clinical trials have typically exhausted standard therapies and often are choosing between a clinical trial and hospice care. Significant symptom burden can result in early trial discontinuation and confound trial outcomes. This study aimed to examine differences in study duration, symptom burden, adverse events (AE), and quality of life (QOL) between those receiving structured palliative care versus usual supportive care. Patients and methods Sixty‐eight patients enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Finally, 23% and 26% of the patients in C1 and C2 died 3 months after discontinuation of the study, but only few were addressed to our palliative care team, which highlight the need for a better evaluation of the patients. While our study did not report any data regarding change in quality of life, a randomised control trial on 68 patients included in early clinical trials showed fewer adverse events and better quality of life for patients receiving palliative care than those in the control group 23…”
Section: Discussionmentioning
confidence: 59%
“…Finally, 23% and 26% of the patients in C1 and C2 died 3 months after discontinuation of the study, but only few were addressed to our palliative care team, which highlight the need for a better evaluation of the patients. While our study did not report any data regarding change in quality of life, a randomised control trial on 68 patients included in early clinical trials showed fewer adverse events and better quality of life for patients receiving palliative care than those in the control group 23…”
Section: Discussionmentioning
confidence: 59%
“…There is also an increased recognition of the benefits of implementing palliative care for patients as they undergo phase 1 trials, despite their previous ineligibility as a result of receiving disease-directed therapy. 19,[27][28][29][30] Early engagement of palliative care might offset burden of care for caregivers by helping with the aggressive management of patient symptoms while addressing goals of care in the context of a lifelimiting illness. 30 This study reveals that caregivers are compelled to unequivocally support patients' decisions to pursue phase 1 trials for advanced cancer out of a sense of urgency to achieve disease stabilization and in order to endorse patient autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…19,[27][28][29][30] Early engagement of palliative care might offset burden of care for caregivers by helping with the aggressive management of patient symptoms while addressing goals of care in the context of a lifelimiting illness. 30 This study reveals that caregivers are compelled to unequivocally support patients' decisions to pursue phase 1 trials for advanced cancer out of a sense of urgency to achieve disease stabilization and in order to endorse patient autonomy. To protect patient autonomy, they withhold their opinions about the trial to avoid influencing the patient's decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These discussions represent an opportunity to introduce specialty PC services when describing the potential for symptom burden, limited life expectancy, and need for psychosocial support. Furthermore, a randomized controlled study of patients actively enrolled in phase 1 clinical trials comparing concurrent structured PC and usual supportive care found that patients with structured PC had fewer adverse events and better quality of life, though not statistically significant 20. As such, it may be worth considering a specialty PC referral be made for a patient and their family at the time of therapeutic clinical trial enrollments, especially in the setting of a high-risk cancer diagnosis.Further studies evaluating the causative factors leading to missed opportunities for early PC involvement are warranted, though our study suggests that clinical trial participation may not contribute to the timing of PC involvement.…”
mentioning
confidence: 99%